Double fluorescence assay via a β-cyclodextrin containing conjugated polymer as a biomimetic material for cocaine sensing. Issue 21 (9th May 2017) - Arslan, Mustafa; Yilmaz Sengel, Tulay; Guler, Emine; Gumus, Z. Pinar; Aldemir, Ebru; Akbulut, Huseyin; Coskunol, Hakan; Timur, Suna; Yagci, Yusuf
Abstract : A double fluorescence based μ-well assay was designed by using a novel biomimetic material (PPP-CD- g -PEG ) for cocaine detection. Abstract : A double fluorescence μ-well assay that exploits a novel conjugated polymer containing cyclodextrin (CD) as the key component is reported. For the construction of the cocaine bioassay, poly( p -phenylene) with CD units in the main-chain and poly(ethylene glycol) side chains (PPP-CD- g -PEG ) was first prepared by Suzuki coupling polymerization and coated on each well as a biomimetic material. Although the polyphenylene backbone is responsible for the fluorescence properties without an additional fluorophore, PEG and CD provide water solubility and selective complexation with cocaine, respectively. A cocaine antibody was used as a secondary recognition compound after labelling with quantum dots (QDs). Most notably, we show that the two-color fluorescence nature of the assay facilitates double measurement from the same sample and the described strategy can be adapted to various sensing systems.